2017
DOI: 10.1007/s11356-017-9777-8
|View full text |Cite
|
Sign up to set email alerts
|

Pb-induced changes in roots of two cultivated rice cultivars grown in lead-contaminated soil mediated by smoke

Abstract: Nowadays, public concerns regarding deleterious effect of lead (Pb) is on rise due to its abundance and toxic effect on plants and other living organisms. In plants, it has no noticeable biological importance but can cause various morphological, physiological, and biochemical malfunctions. To evaluate the remediating potential of plant-derived smoke (Cymbopogon jwarancusa), a pot culture experiment was designed to investigate the physiological, biochemical, metabolic, and antioxidant parameters of roots in lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Excessive accumulation of metals induces the generation of reactive oxygen species (ROS) that cause oxidative stress in plants (Kaur et al, 2015). To ease the detrimental effects of ROS under stress conditions, plants have developed antioxidant defense systems (Zouari et al, 2016;Akhtar et al, 2017) which restrains and reduces the oxidative damage, and enhances the stress resistance in plants (Suzuki et al, 2012). Moreover, sulphur dioxide (SO2), a highly detrimental pollutant in the vehicular emissions also causes the generation of ROS and rise in the activity of antioxidants (Li & Yi, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Excessive accumulation of metals induces the generation of reactive oxygen species (ROS) that cause oxidative stress in plants (Kaur et al, 2015). To ease the detrimental effects of ROS under stress conditions, plants have developed antioxidant defense systems (Zouari et al, 2016;Akhtar et al, 2017) which restrains and reduces the oxidative damage, and enhances the stress resistance in plants (Suzuki et al, 2012). Moreover, sulphur dioxide (SO2), a highly detrimental pollutant in the vehicular emissions also causes the generation of ROS and rise in the activity of antioxidants (Li & Yi, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to previously discussed parameters, alleviation was further supported by increase in cell membrane stability of smoke primed rice seedlings compared to non-treated ones [ 40 ]. Furthermore, flooding stress tolerance [ 14 ] and reduction in the inhibitory effects of heavy metals on plant growth [ 15 ] are also well documented. This characteristic can be interpreted as plant-derived smoke is not only responsible for promoting plant growth but also strategically involved in protecting plants against abiotic stresses.…”
Section: Components In Plant-derived Smokementioning
confidence: 99%
“…Furthermore, a supply of plant-derived smoke solutions during flooding stress led to the flooding recovery of soybean after the removal of water [ 14 ]. It reduced the inhibitory effects of heavy metal, drought, salinity, and high/low temperature stresses on plant growth [ 15 ]. These results indicated that plant-derived smoke is a growth enhancer, reducer of inhibitory effect of environmental stresses, and a possible plant-growth fertilizer.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Rao et al (2018) suggested that seeds with ultrasonic treatment improved the content of proline and soluble protein and enhanced the activities of SOD, CAT, and ascorbate peroxidase under Pb toxicity, which ultimately increased grain yield. Akhtar et al (2017) indicated that smoke could lessen Pb stress in two rice cultivars grown in Pbcontaminated soil. Nitrogen (N) is one of the important nutrients for plant growth, and N fertilizer played an important role in regulating grain yield, protein content, and grain quality in rice (Ali et al 2020;Jiang et al 2019;Pan et al 2017a;Mo et al 2018Mo et al , 2019aMo et al , 2019b.…”
Section: Introductionmentioning
confidence: 99%